Fostering Awareness of Christian Moral Rights and Obligations For Catholic Youth Based on the Teachings of the Catholic Church and the Concept of Actus Humanus - Gonti Simanullang (Abdimas Paspama, 2023)
The development of digital technology, individualistic culture, and moral relativism are influencing the way young people understand freedom, rights, and social responsibility. This condition gives rise to a tendency to demand personal rights without being balanced by the awareness of carrying out moral obligations to God, others, the Church, and society. This Community Service activity aims to increase the understanding and awareness of young Catholics regarding the relationship between rights, obligations, freedoms, conscience, and responsibilities based on the teachings of the Catholic Church and the concept of actus humanus. The implementation of activities uses an educational, pastoral, participatory, and reflective approach through interactive lectures, group discussions, Scripture reflection, moral case studies, and the preparation of action plans. Evaluation was carried out using pre-test and post-test, observation sheets, case study assessments, participant reflections, and satisfaction questionnaires. The draft results show an increase in the average score from 55.5 to 84.3. Participants also showed better ability to distinguish moral rights and obligations, connect freedom with responsibility, analyze moral issues, and formulate service commitments. This activity emphasizes that actus humanus-based coaching is able to help young people understand that moral action always involves knowledge, freedom, choice, and accountability. The sustainability of activities is directed through OMK mentoring, the use of modules, periodic reflection meetings, and evaluation of pastoral involvement.